Implementation and Behavioral Engineering of 3R (Reduce, Reuse, Recycle) among the Academic Community of FISIP Universitas Lampung through the Application of the TigaR Waste Management System - Arif Sugiono; Ahmad Riza Faizal; Amril Ma’ruf Siregar; Eka Yuda Gunawibawa (PT FORMOSA CENDEKIA GLOBAL, 2026)
Universitas Lampung has implemented the green campus concept through environmentally oriented policies, including the establishment of an Integrated Waste Management Facility (TPST) and participation in the UI GreenMetric ranking system. However, the 2023 GreenMetric evaluation indicated that the university’s inorganic waste management score remained low and unchanged from the previous year. This study aimed to implement and engineer 3R (Reduce, Reuse, Recycle) behavior among the academic community of FISIP Universitas Lampung through the application of a digital waste management platform called tigaR. The study employed a mixed-methods approach involving surveys, interviews, usability testing, and Focus Group Discussions (FGD). The tigaR application was developed using a Deposit-Return System (DRS) model focusing on tumbler usage and plastic bottle waste management. The findings showed that the application increased user participation in waste reduction and encouraged environmentally responsible behavior within the campus environment.